In vitro and in vivo antibacterial efficacy of bacteriophage combined with tigecycline against carbapenem-resistant Klebsiella pneumoniae and characterization of phage resistant mutants - Zhu, Rui; Wang, Ruilin; Fei, Bing; Lu, Ruici; You, Xiaojuan; Liu, Xinwei; Wang, Chunxia; Li, Yongwei (Frontiers in Cellular and Infection Microbiology, 2025)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) has emerged as a critical global public health threat, characterized by high infection rates, elevated mortality, and limited therapeutic options. In this study, we isolated and characterized a novel bacteriophage (phage), designated as HZJ31, which exhibited potent lytic activity against CRKP strains. Phylogenetic and genomic analyses revealed that phage HZJ31 belongs to the order Caudovirales and lacks virulence factors, antibiotic resistance genes, and lysogeny-related elements, supporting its suitability for therapeutic applications. Phage HZJ31 exhibits remarkable anti-biofilm activity by preventing biofilm formation and disrupting established biofilms, with bacterial reduction rates exceeding 70% (P<0.05). In combination with Tigecycline, it significantly enhanced bactericidal efficacy, delayed the emergence of phage resistant mutants, and improved survival rates in Galleria mellonella larvae infection models. Compared to the bacterial-infected group, which had 80% larval mortality at 96 h, treatment with HZJ31 or TGC alone led to 50% and 60% survival, while their combination improved survival to 70% (P < 0.05). Notably, the phage-resistant mutant, which emerged due to capsule loss, resulted in reduced growth and virulence, while regaining sensitivity to certain antibiotics (such as gentamicin), indicating a fitness cost associated with phage resistance. Collectively, these findings provide valuable insights into phage-antibiotic synergy and underscore the promising clinical potential of phage HZJ31 as a therapeutic agent against CRKP infections.